Correlation analysis between tomato price and wheat price in Brazil in the period 2010 to 2018 (Research, Society and Development, 2020)
Wheat and tomato are products that are present in Brazilian food, being complementary goods when industrialized and used to prepare ready and fast foods. Thus, this work seeks to identify whether the price of tomatoes and the price of wheat has a relation. The methodology used is a quantitative approach, using statistical tools. The results showed a linear correlation of 0.389 (or 38.69%) between tomato and wheat prices, and regression analysis showed that a 1% increase in the price of wheat implies an increase of 0.601 % in the price of tomato. It is concluded that the results corroborated to the expected that the price of wheat and tomato has a positive relation, being considered complementary goods when used in the preparation of fast foods.